¡Vamos! Let's go to the market - Raúl the Third, 1976- (The world of ¡vamos!, 2019)
What will Little Lobo see at the Mercado today? As he and his dog, Bernabé, make deliveries, he stops to visit his friends who sell candy, comic books, puppets, and more. There are so many things to do and see! Join Little Lobo and Bernabé for a visit to a bustling border town market and learn some Spanish along the way! --